2009
DOI: 10.1038/sj.bjc.6605405
|View full text |Cite|
|
Sign up to set email alerts
|

Profiling of high-grade central osteosarcoma and its putative progenitor cells identifies tumourigenic pathways

Abstract: BACKGROUND: Osteosarcoma is the most prevalent primary malignant bone tumour in children and young adults, with poor survival in 40% of patients. To identify the signalling pathways involved in tumourigenesis, we compared gene expression in osteosarcoma with that in its presumed normal counterparts. METHODS: Genome-wide expression profiles were generated from 25 high-grade central osteosarcoma prechemotherapy biopsies, 5 osteoblastomas, 5 mesenchymal stem cell (MSC) populations and these same MSCs differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 29 publications
3
74
1
Order By: Relevance
“…Such studies were reported for liposarcoma [111], chondrosarcoma [112], osteosarcoma [52] and leiomyosarcoma [32]. Likewise, osteosarcoma and ARMS have been modeled by the establishment of relevant oncogenic hits in nearly differentiated cells of the osteoblastic and myoblastic lineages, respectively [34,35,76].…”
Section: Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies were reported for liposarcoma [111], chondrosarcoma [112], osteosarcoma [52] and leiomyosarcoma [32]. Likewise, osteosarcoma and ARMS have been modeled by the establishment of relevant oncogenic hits in nearly differentiated cells of the osteoblastic and myoblastic lineages, respectively [34,35,76].…”
Section: Open Questionsmentioning
confidence: 99%
“…Conversely, restoration of WNT signaling in MFH cells allowed them to differentiate along different mesenchymal lineages [51]. Furthermore, it was reported that key components of the Wnt signaling pathway are downregulated in osteosarcoma as compared to normal hMSCs and hMSCs differentiated into osteoblasts [52]. Interestingly, the role of WNT signaling in sarcomas seems to differ from its role in carcinomas because hMSC transformation and sarcomagenesis are associated with WNT signaling inhibition while different models of carcinomas are linked to activating mutations in components of the WNT pathway [51].…”
mentioning
confidence: 99%
“…(18) This same research group has performed expression profiling of these cell types and has suggested that downregulation of Wnt signaling has an important role in osteosarcoma pathogenesis. (20) When the Wnt pathway was activated using a GSK3b inhibitor in osteosarcoma cell lines, proliferation was inhibited, and osteogenic differentiation was observed. (21) This is further supported by the observation that patients with osteosarcoma have higher serum levels of Dkk-1, a secreted inhibitor of the canonical Wnt pathway.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%
“…Some studies indicate that osteosarcoma cells also arise from progenitor stem cells, although the particular stem cell has not been identified but it is thought to be an osteoprogenitor cell capable of differentiating into phenotypes seen in cartilage and bone [9,17,19,20,55]. We suggest the stem cells giving rise to the cancer may be more primitive than an immediate progenitor cell, ie, a multipotent stem cell.…”
Section: Introductionmentioning
confidence: 98%
“…Osteosarcomas reportedly contain cells that express markers for mesodermal tissue such as cartilage and muscle [23], and ectodermal tissue markers like cytokeratin [27]. Ewing's sarcoma contains cells with mesenchymal, epithelial, and neural features [9,10,46]. Sarcoma cells promote neuronal and glial differentiation [19,21,22], which means that the cells with these markers in Ewing's sarcoma could have arisen from nonsarcoma cells.…”
Section: Introductionmentioning
confidence: 99%